La relación de los componentes de la dinámica económica argentina y el capital financiero entre 2002 y 2012 - Marisa Leonor BORDÓN-OJEDA (Revista Iberoamericana de Estudios de Desarrollo)
The combination of certain economic policies and a positive external situation contributed to high growth rates of the Argentine economy and a lower external debt during the first years of post-convertibility. The objective of this paper is to verify if the financial capital kept a central position in the Argentine economic process in the first decade of post-convertibility, by analysing the relations between the financial capital and the different areas of the economic dynamics. This central position was characterized by the ability of the financial capital to condition policy making decisions, partial disconnection with productive activity and high profitability. The study was carried out through a historical structural approach, limiting the areas of economic dynamics to its most relevant variables in the explanation of the functioning of Argentine economy.